RUMINAL DEGRADABILITY CHARACTERISTICS IN VEGETABLE PROTEIN SOURCES OF PAKISTAN - I. B. Marghazani; M. A. Jabbar; T. N. Pasha; M. Abdullah (Journal of Animal and Plant Sciences, 2013)
Fifteen different vegetable protein sources found in Pakistan were evaluated for ruminal degradability characteristics through in situ procedure using rumen fistulated Nili-Ravi buffalo steer. Samples of soybean meal, corn gluten meal 60%, maize gluten feed, guar meal, sunflower meal, rapeseed meal, rapeseed cake, canola meal, cottonseed cake, cottonseed meal, coconut cake, coconut meal, palm kernel cake, almond cake and sesame cake were obtained from 10 different locations. Crude protein (CP) ruminal degradability was determined at 0, 3, 6, 12, 24 and 48 hours in triplicate. Data obtained at different hours of ruminal incubation were fitted to Orskov and McDonald equation to determine fractions a, b, degradation rate and effective degradability at 2, 5 and 8 percent. In CP degradation kinetics, fractions a, b, and degradation rate were different (P<0.001). Effective CP degradability at different rumen passage rates (2, 5, 8 %) was also affected (P<0.001) by the source of protein. It was concluded that at 5% rumen passage rate, coconut meal and corn gluten meal showed least degradability and therefore can be incorporated in growing and lactating ruminant rations for higher bypass protein value.
Keywords: Ruminal degradability; vegetable protein sources; undegradable protein; Nili-Ravi buffalo